2006
DOI: 10.1111/j.1559-3584.2006.tb00469.x
|View full text |Cite
|
Sign up to set email alerts
|

Emissions Trading for Ships — a European Perspective

Abstract: Shipping is under growing pressure to reduce its emissions to air. Pressures exist at both a local (e.g. port environment) and global (transboundary pollution transport and greenhouse gas issues). Regulation is gradually coming into effect internationally (IMO) and through regional actions in Europe. North America may be next. Shipping would benefit from flexible schemes to achieve better environmental performance and to allow investments to be made in the most cost effective areas. This brief paper sets out s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In contrast, the fuzzy analysis indicated that long payback period is the most important barrier, although high investment cost remained one of the most important causal factors in the model. In other words, high investment cost is a critical barrier to including ports in the EU ETS according to both empirical studies (Davies, 2006;Dai et al, 2018Dai et al, , 2019Peng et al, 2019;Gianoli and Bravo, 2020;Piccoli et al, 2021) and the views of selected experts in managerial position in certified green ports in T€ urkiye. In short, ports have financial concerns regarding the potential benefits from participating in the EU ETS carbon trading market.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, the fuzzy analysis indicated that long payback period is the most important barrier, although high investment cost remained one of the most important causal factors in the model. In other words, high investment cost is a critical barrier to including ports in the EU ETS according to both empirical studies (Davies, 2006;Dai et al, 2018Dai et al, , 2019Peng et al, 2019;Gianoli and Bravo, 2020;Piccoli et al, 2021) and the views of selected experts in managerial position in certified green ports in T€ urkiye. In short, ports have financial concerns regarding the potential benefits from participating in the EU ETS carbon trading market.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the fuzzy analysis indicated that long payback period is the most important barrier, although high investment cost remained one of the most important causal factors in the model. In other words, high investment cost is a critical barrier to including ports in the EU ETS according to both empirical studies (Davies, 2006; Dai et al. , 2018, 2019; Peng et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations